Committee System in Nigerian Public Tertiary Institutions: Problems and Way Forward - Niyi Jacob Ogunode; Ruth Ibukun Mcbrown (Researchparks Publishing, 2022)
The committee system is a part and parcel of the tertiary institutions. The committee is the micro-element representative of the entire system cut out to carry out special assignments that are key to the development of the institutions. Committees in the tertiary institutions in Nigeria are faced with many problems hindering their effectiveness. This paper examined the various problems hindering the effectiveness of committees in the tertiary institutions in Nigeria. Content analysis method was adopted to select the print and online literature on committee system in the higher institutions. The paper concludes that problem solving, fast decision making and participation in school governance and promotion of external relationship are the vital benefits of the committee system to the tertiary institutions. Also, the paper identified inadequate funding, overlapping membership, frequent cancellation of meetings, delay in the decision-making process, non-implementations of committee’s recommendation and bias in selection of committee members are some of the problems hindering the development of committees in the Nigerian tertiary institutions. The paper concluded by recommending adequate funding for committees, constant capacity building for committee members, merit selection of committee’s chairs and members as well as implementation of committee’s report recommendations.